1995
DOI: 10.1070/rc1995v064n11abeh000189
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the adsorption of water molecules on carbon adsorbents

Abstract: The first-order correct-boundary Coulomb-Born distorted-wave approximation is used to study the double-electron capture by protons from the ground-state helium atoms at intermediate and high impact energies. The differential double capture cross sections are obtained as a function of the projectile scattering angle and the total cross sections as a function of the impact energy. In the considered range of impact energy, our calculation shows that although the results are not so sensitive to the static inter-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…An extremely important prerequisite to the studies of the interaction of water and methanol with carbon materials is the thermal pre-processing of the samples (Vartapetyan and Voloshchuk, 1995;Tarasevich et al, 1998;Kiselev and Yashin, 1967). In our experiments it was shown that pre-processing of the GTCB at 200 • C resulted in the fact that no elution peaks were observed after the injection of first few portions of water into the column packed with the adsorbent, which indicates that at the initial stage the water molecules are chemisorbed by the sorbent.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…An extremely important prerequisite to the studies of the interaction of water and methanol with carbon materials is the thermal pre-processing of the samples (Vartapetyan and Voloshchuk, 1995;Tarasevich et al, 1998;Kiselev and Yashin, 1967). In our experiments it was shown that pre-processing of the GTCB at 200 • C resulted in the fact that no elution peaks were observed after the injection of first few portions of water into the column packed with the adsorbent, which indicates that at the initial stage the water molecules are chemisorbed by the sorbent.…”
Section: Methodsmentioning
confidence: 74%
“…Table 1) characteristic of these materials are formed mainly by the gaps between adjacent lamellar particles. However, during thermal processing, a rolling of graphite particles can take place, which results in the formation of void tube-like structures with an internal radius r ≈ 25 nm (Vartapetyan and Voloshchuk, 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 demonstrates the appearance and growth of two water proton NMR lines. Initially only line B appeared, which obviously demonstrates that the adsorption process begins in micropores, which serve as primary adsorption centers and accumulate water molecules (15,(20)(21)(22). Line A does not appear until the integral intensity of line B reaches the saturation value equal to that for suspension.…”
Section: General Considerationsmentioning
confidence: 99%
“…Most of the experimental studies on adsorption of H 2 O by microporous carbons have shown that the surface functional groups play the main role [140,[161][162][163][164], and some of these studies have investigated the role of surface groups by exposing carbon materials to controlled oxidative treatments [156,164].…”
Section: Water Adsorption In Carbon Materialsmentioning
confidence: 99%